2012
DOI: 10.1016/s1995-7645(12)60141-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of various honey types of Algeria against Staphylococcus aureus and Streptococcus pyogenes

Abstract: Algeria honey, in-vitro, possess antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 14 publications
2
37
0
2
Order By: Relevance
“…The maximum zone of inhibition was observed in S. typhii and minimum inhibition was recorded in S. flexneri. Previously, several of the report on anti-microbial activity of gorgonian extract have been studied and published [21][22][23][24][25][26][27][28][29][30][31][32] . Sastry et al [22] have reported ethyl acetate extract of J. juncea showed enhanced antibacterial activity against B. subtilis, B. pumilis and E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum zone of inhibition was observed in S. typhii and minimum inhibition was recorded in S. flexneri. Previously, several of the report on anti-microbial activity of gorgonian extract have been studied and published [21][22][23][24][25][26][27][28][29][30][31][32] . Sastry et al [22] have reported ethyl acetate extract of J. juncea showed enhanced antibacterial activity against B. subtilis, B. pumilis and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Congo red dye (0.8 g/L) was also prepared simultaneously and added to warm (55 °C ) BHI agar. The media was poured on to Petri dishes, inoculated and incubated for [24][25][26][27][28][29][30][31][32][33][34][35][36] h at 37 °C .…”
Section: Biofilm Formation In Congo Red Agarmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread plate count technique was used (26) , 1ml of each honey sample was mixed with 1ml of the sterile tween-saline solution (0.9% w/v NaCl in distilled water containing 0.1% v/v tween 80, adjusted at pH 7) on a vortex (type paramix II No. 65, West Germany) for 3min, and 2-fold serial dilutions were made in the same diluent.…”
Section: Honey Samplesmentioning
confidence: 99%
“…According to (26) , the antibacterial activity was classified as: not sensitive (<8 mm); sensitive (8 to 14mm); very sensitive (15 to 19mm) and extremely sensitive (>20mm). Table ( 4) shows that the antimicrobial activity of the honey samples against the pathogenic microorganisms decreased upon dilution.…”
Section: Antimicrobial Assay Of Non-irradiated and Irradiated Honey Smentioning
confidence: 99%